Teenage Mutant Ninja Turtles: Mutant Mayhem - Edebiri, Ayo; Byrne, Rose; Demetriou, Natasia; Cena, John; Rudd, Paul; Esposito, Giancarlo; Rudolph, Maya; Eastman, Kevin B.; Abbey, Micah; Laird, Peter; Noon, Brady; Cheng, Long, 1954-; et al. ([United States] : Paramount Pictures, 2023)
After years of being sheltered from the human world, the Turtle brothrs set out to win the hearts of New Yorkers and be accepted as normal teenagers through heroic acts. Their new friend April O'Neil helps them take on a mysterious crime syndicate, but they soon get in over their heads when an army of mutants is unleashed upon them.
"Finally, a "Teenage Mutant Ninja Turtles" movie that really earns a "Cowabunga!"--USA Today
"It imbues a thrill of discovery while still feeling like a comfortable visit with old friends."--San Francisco Chronicle
"They lurk, leap and soar across a neon-streaked New York City that, for all its digital rendering, feels as fresh and hand-crafted as a made-to-order Brooklyn pizza."--Los Angeles Times
DVD.
Based on the Teenage Mutant Ninja Turtles characters created by Peter Laird and Kevin Eastman.
new dvd 2023 winter.
Director, Jeff Rowe, Kyler Spears.
:Voices: Micah Abbey, Shamon Brown Jr., Nicolas Cantu, Brady Noon, Ayo Edebiri, Maya Rudolph, John Cena, Seth Rogen, Rose Byrne, Natasia Demetriou, Giancarlo Esposito, Jackie Chan, Ice Cube, Paul Rudd, Austin Post, Hannibal Buress.
MPAA rating: PG.
Keywords: Action and adventure films; Martial arts films; Children's films; Fantasy films; Superhero films